2015
DOI: 10.1093/humupd/dmv041
|View full text |Cite
|
Sign up to set email alerts
|

The role of infection in miscarriage

Abstract: BACKGROUNDMiscarriage is the spontaneous loss of a pregnancy before 12 weeks (early miscarriage) or from 12 to 24 weeks (late miscarriage) of gestation. Miscarriage occurs in one in five pregnancies and can have considerable physiological and psychological implications for the patient. It is also associated with significant health care costs. There is evidence that potentially preventable infections may account for up to 15% of early miscarriages and up to 66% of late miscarriages. However, the provision of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
256
1
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(303 citation statements)
references
References 192 publications
4
256
1
22
Order By: Relevance
“…Установлено, что наличие лактобацилл, продуцирующих высокий уровень перекиси водорода, ассоциировано с низкой частотой БВ, преждевременных родов и послеродовых инфек ционных осложнений [10,11]. Изучение генотипических и биохимических свойств ваги-нальных лактобацилл показало, что L. crispatus, L. jensenii и L. vaginalis представляют собой наиболее часто встречающиеся виды перекиси продуцирующих лактобацилл [12].…”
Section: вагинальный микробиомunclassified
“…Установлено, что наличие лактобацилл, продуцирующих высокий уровень перекиси водорода, ассоциировано с низкой частотой БВ, преждевременных родов и послеродовых инфек ционных осложнений [10,11]. Изучение генотипических и биохимических свойств ваги-нальных лактобацилл показало, что L. crispatus, L. jensenii и L. vaginalis представляют собой наиболее часто встречающиеся виды перекиси продуцирующих лактобацилл [12].…”
Section: вагинальный микробиомunclassified
“…Studies conducted over the last 30 years have demonstrated a correlation between an increased rate of adverse pregnancy outcomes with infection by certain microbial agents [70]. Historical, experimental, and epidemiological evidence supports the concept that Brucella infection in animals is a significant risk factor for abortion [19, 21•, 22].…”
Section: Mechanism Of Brucella-induced Abortion In Animals and Humansmentioning
confidence: 99%
“…It is believed that potentially preventable infections can account for up to 15% of early miscarriages, and for up to 66% of late miscarriages. And, chronic persistent endometritis coexists with every third pregnancy and is detected in more than 60% of cases of recurrent miscarriage [2].…”
Section: Introductionmentioning
confidence: 99%